Development and Characterization of Functional O/W Emulsions with Chia Seed (Salvia hispanica L.) by-Products - Julio, Luciana Magdalena (2020)
Physicochemical properties of O/W emulsions containing functional ingredients (high ω-3 fatty acid content, protein, and soluble fiber) from chia seeds with different protein– carbohydrate combinations (sodium caseinate-lactose, sodium caseinate-maltodextrin, and chia protein-rich fraction-maltodextrin) and chia mucilage were studied. Sodium caseinate with lactose or maltodextrin produced O/W emulsions with small droplet size, high uniformity in droplet size distribution, negatively charged droplets (pH 6.5), pseudoplastic behavior, and high physical stability. Emulsions with chia protein-rich fraction presented wider droplet size distribution and higher D3.2 values than the previous ones, recording a Newtonian behavior. The addition of chia mucilage affected the rheological characteristics of emulsions.